Prevalence of polypharmacy and potentially inappropriate medication use in older lung cancer patients: A systematic review and meta-analysis - Fangyuan Tian; Fangyuan Tian; Zhaoyan Chen; Dan Zhou; Li Mo (Frontiers Media S.A., 2022)
Objectives: In older lung cancer patients, polypharmacy and the use of potentially inappropriate medications (PIMs) are commonly reported, but no systematic review or meta-analysis has been carried out to ascertain the prevalence and risk variables in this group. This study aimed to identify the prevalence of polypharmacy, PIMs and associated risk variables in older lung cancer patients.Methods: We searched for articles from the beginning to February 2022 in PubMed, Embase, and Web of Science that related the use of PIMs and polypharmacy by older lung cancer patients (PROSPERO Code No: CRD42022311603). Meta-analysis was performed on observational studies describing the prevalence and correlation of polypharmacy or PIMs in older patients with lung cancer.Results: Of the 387 citations, 6 articles involving 16,890 patients were included in the final sample. In older lung cancer patients pooled by meta-analysis, 38% and 35% of PIMs and polypharmacy, respectively. The prevalence of PIMs was 43%, 49%, and 28%, respectively, according to the 2019 AGS Beers criteria, 2014 screening tool for older people's prescriptions/screening tool for alerting to the proper therapy (STOPP/START criteria) criteria, and other criteria.Conclusion: This systematic review and meta-analysis demonstrated a high prevalence of polypharmacy and PIMs among older lung cancer patients. Therefore, it is essential to take rational interventions for older lung cancer patients to receive reasonable pharmacotherapy.Systematic Review Registration: [https://www.crd.york.ac.uk/PROSPERO/], identifier [CRD42022311603].